0473 The Relationship Between Frailty and Sleep-Disordered Breathing in an Otolaryngology-Based Sleep Population. (27th April 2018) - Schell, A; Baniak, L; Hall, D; Soose, R; Strollo, P
Abstract: Introduction: Frailty is a syndrome of diminished physiologic reserve that has been associated with adverse outcomes post-surgery. The aims of this study were to establish the prevalence of frailty in an Otolaryngology-based sleep population and explore the relationships between frailty and sleep measures. Methods: We performed a retrospective review of new patients presenting to an Otolaryngology sleep clinic who underwent diagnostic sleep testing. Data pertaining to demographics, frailty (Risk Analysis Index [RAI]), sleep-disordered breathing (apnea-hypopnea index [AHI]), and daytime sleepiness (Epworth Sleepiness Scale [ESS]) were abstracted. RAI scores range from 0 to 81 (higher score indicates a greater degree of frailty; RAI ≥ 21 = frail). Descriptive statistics, Student's independent t -tests, Chi square tests, and Spearman correlations were computed. Significance was set at p ≤ .05. Data are reported as median ±IQR. Results: A total of 130 patients met inclusion criteria (53.8% male, median age 49 years [35.8–60.3], BMI 30.9 kg/m 2 [27.2-24.9], and AHI 12 events/hour [5–24]). Overall, 43% (n=56) of the sample had moderate or severe OSA (AHI > 15), and 39.2% (n= 51) reported excessive daytime sleepiness (ESS > 10). Only 3.8% (n= 5) were categorized as frail according to the RAI. Of those, all had moderate or severe OSA. Those with moderate to severe OSA were significantly older, more obese, more likely to be male, and more likely treated for hypertension compared to those with mild or no OSA, (all p -values ≤ .05). Higher RAI scores were significantly correlated with higher AHI (rho = .204, p < 0.02) but not with BMI or daytime sleepiness. Conclusion: Although frailty does not appear to be highly prevalent within an Otolaryngology-based sleep population, increasing RAI was significantly associated with greater AHI in these patients. In this study, all patients categorized as frail had diagnoses of moderate or severe sleep apnea. Support (If Any): Translational Sleep Medicine T32 HL82610.